PEMANFAATAN LIMBAH SERBUK MARMER DAERAH TRENGGALEK SEBAGAI BAHAN TAMBAH PADA PEMBUATAN PAVING BLOCK - Erick Eka Perkasa; Bachtiar, Gina; Chrisnawati, Yusfita (LPPM, Universitas Negeri Jakarta, 2020)
This research aimed to find out the maximum compressive strength of paving block with marble waste powder as additive based on SNI 03-0691-1996 for concrete brick class I as wall pair including outside view, physical requirement (compressive strength and water absorption). This research using experimental method to test the object that use 0%, 5%, 10%,15% and 20% of marble waste powder. The object size was 21 cm x 10,5 cm x 8 cm, with total sample was 100 paving block. Each percentage (5 samples for physical test,10 for mechanical test and 5 as reserve ). The testing performed when paving block 28 days old. The research results show to raise the value strong press paving block by the addition of waste the marble to 10 %.Strong press maximum objects test is at the percentage the addition of waste the marble 10 % with strong press of 26,97 mpa. To absorption capacity water look a decrease in with increase in the percentage the addition of waste the marble to 10 % .Power drain employ water maximum objects test is at the percentage the addition of waste the marble 10 % with absorption capacity of water amounting to 5 %. Keywords: waste marble powder, compressive strength, water absorbtion, paving block, admixture